Attitudes of Students at Al-Mumtaz Islamic Intermediate School in Pontianak West Kalimantan Towards The Process of Arabic Learning and Teaching - Nurhayati, Raden; Buhori, Buhori; Syahrani, Syahrani (Borneo Journal of Language and Education, 2023)
This research is intended to find out about the process of learning Arabic at SMPIT Al-Mumtaz Pontianak, West Kalimantan, and the attitudes of students towards the process of Arabic learning and teaching. This research is important to do considering that students' attitudes toward learning play such an important role in motivating responses, improving performance, strengthening interest, and improving learning outcomes. Students' attitudes towards the learning process can affect student learning outcomes, so when students have a positive attitude and feel confident in their abilities, they will be able to achieve better results. The method used in this research is descriptive-qualitative. To process the results, the percentage formula is used. The results of this study found that the process of learning Arabic at SMPIT Al-Mumtaz had been carried out well, from the planning, implementation, and rating processes. Meanwhile, students' attitudes toward learning Arabic were in a good category.